Primary dedifferentiated liposarcoma of the ovary: expanding the surgical management spectrum with a different resection extent than existing reports – a case report and literature review - Liang, Hao; Wen, Mingxia; Liang, Xuzhi; Lv, Zili; Fan, Jiangtao (Frontiers in Oncology, 2025)
BackgroundDedifferentiated liposarcoma (DDLPS) is a relatively common type of liposarcoma, typically occurring in the retroperitoneum and limbs. It is rarely found in the female reproductive system, leading to the absence of a standard treatment protocol for primary ovarian dedifferentiated liposarcoma. This case presents a personal experience-based approach, as there is a lack of standard treatment guidelines, relying on treatment consensus for more common locations and decades of clinical experience.Case presentationThis case report describes a 55-year-old woman who was admitted due to a gradually enlarging mass in the right lower abdomen, accompanied by bloating and abdominal pain. Physical examination revealed a palpable abdominal mass. Gynecological ultrasound showed a hyperechoic mass measuring 135*128*91mm in the pelvic-abdominal cavity. CT imaging suggested a large cystic and solid mixed liposarcoma originating from the ovary, with unclear delineation of the uterine fundus and slight compression of surrounding organs. Pelvic MRI revealed an irregular mass approximately 10.7cm×12.6cm×12.2cm, with slightly prolonged T1 and heterogeneous T2 signals, showing fat signal in the right fatty tissue, suggesting invasion of the uterine wall by liposarcoma. The patient then underwent open surgery, and postoperative pathology with immunohistochemistry confirmed dedifferentiated liposarcoma. FISH testing was positive for MDM2, confirming the diagnosis of ovarian-origin dedifferentiated liposarcoma. Although the patient refused chemotherapy, she has been followed up every three months, and the current follow-up shows no signs of tumor recurrence.ConclusionOvarian dedifferentiated liposarcoma is an extremely rare condition, with surgery being the preferred treatment method. This report presents a rare case of ovarian dedifferentiated liposarcoma, providing a reference for clinical diagnosis and treatment. Through collaboration between gynecology, pathology, and imaging departments, the accuracy of the diagnosis and comprehensiveness of treatment were ensured. Long-term follow-up of the patient provided valuable insights into the recurrence and prognosis of the disease.